Crocodile Egg Collection in Tamil Nadu - Whitakeb, Romulua (Indian Forester, 1979)
In 1976, the Madras Snake Park carried out marsh crocodile egg collection in Tamil Nadu with the co-operation of the Tamil Nadu Forest Department. Eggs were collected at Amaravathi Reservoir, Sathanur Reservoir, Killikuci (Srirangam) Childmbaram Waterworks and transported to the hatchery at Madras Snake Park. Details of egg collection methodology and transport are outlined. Description of incubation and batching are given. Results of the ]976 crocodile egg laying season are presented.